Evaluation of Forest and Climate Change Empowerment Programs of Long Laai Village, Kecamatan Segah Berau District: Evaluasi Program Pemberdayaan Forest and Climate Change Programme Desa Long Laai Kecamatan Segah Kabupaten Berau - Anye, Herman; Suryaningsih, Novita (Progress In Social Development, 2021)
ABSTRACT: The community participation program in conserving village forests is carried out by the Forest and Climate Change Program of Long Laai Village. Indonesia's forest is one of the third largest tropical forests in the world and is ranked second in terms of diversity. From an ecological, economic and social perspective, it turns out that the level of forest destruction in Indonesia is still relatively high from year to year due to uncontrolled exploitation activities carried out massively without paying attention to sustainability and sustainability. Kalimantan is one of the lungs of the world whose forest area is 40.8 million hectares. According to data released by the forestry department, the deforestation rate in Kalimantan from 2000 to 2005 reached around 1.23 million hectares. Berau District has an area of 2,194,299,525 hectares consisting of protection forest, limited production forest, permanent production forest, conservation forest and other areas of use. The successes and failures achieved by the community and the Forest and Climate Change program and the supporting and hindering factors for the program's running are a village approach strategy to raise community awareness in maintaining and utilizing forest products. ABSTRAK: Program partisipasi masyarakat dalam melestarikan hutan desa dilaksanakan oleh Forest and Climate Change Programme Desa Long Laai. Hutan Indonesia merupakan salah satu hutan tropis terluas ketiga di dunia dan ditempatkan pada urutan kedua dalam hal tingkat keanekaragaman. Dari sisi ekologi, ekonomi dan sosial ternyata tingkat kerusakkan hutan di Indonesia masih relatif tinggi dari tahun ketahun diakibatkan kegiatan eksploitasi yang tidak terkendali dan dilakukan secara masif tanpa memperhatikan kelestarian serta keberlanjutan. Kalimantan adalah salah satu paru-paru dunia luas hutannya yaitu, 40,8 juta hektar. Menurut data yang dikeluarkan departemen kehutanan angka deforestasi Kalimantan pada tahun 2000 sampai 2005 mencapai sekitar 1,23 juta hektar. Kabupaten Berau memiliki luas wilayah 2.194.299,525 Ha yang terdiri dari Hutan Lindung, Hutan Produksi Terbatas, Hutan Produksi Tetap, Hutan Konservasi, dan Areal penggunaan Lain. Keberhasilan dan kegagalan yang dicapai masyarakat dan Forest and Climate Change programme dan faktor pedukung dan penghambat jalannya program ada strategi pendekatan desa untuk membangkitkan kesadaran masyarakat dalam menjaga dan memanfaatkan hasil hutan.